Silanization of ZnO nanofibers by tetraethoxysilane. Issue 40 (4th July 2017) - Khan, Shakeel; Rasheed, Muhammad Asim; Rafiq, Muhammad Aftab; Shah, Gul Bali; Rehman, Wajid; Jamil, Arifa; Khan, Yaqoob
ABSTRACT: Zinc oxide (ZnO) nanofibers are synthesized by electrospinning technique and then silanized to tailor its structural, optical, and electrical properties. The modification of ZnO nanofibers by chemical treatment of tetraethoxysilane (TEOS) is clearly evident from the appearance of relevant Fourier transform infrared peak at about 1000 cm −1 corresponding to ZnOSi bond. The height of this peak increases linearly with increase in concentration of silane up to 400 μL, and afterward become plateau up to 500 μL. Diffuse reflectance spectroscopy measurement shows that band gap decreases from 3.35 eV for pure zinc oxide nanofibers to 3.11 eV with successive increase in concentration of TEOS from 100 to 500 μL. The electrical characteristics of modified ZnO nanofibers are analyzed by impedance spectroscopy. It is observed that impedance of ZnO nanofibers increases (resistance from 1.69 × 10 8 to 2.618 × 10 9 ohm and capacitance from 2.043 × 10 −12 to 7.618 × 10 −13 F) with increase of TEOS concentration. This study provides guidelines for tailoring the electrical properties of ZnO nanofibers. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45378. Abstract :